(√3+√7) (√3-√7) simplyfy
Answers
Answered by
2
Answer:
-4
Step-by-step explanation:
we shall use,(a+b)(a-b)=a^2-b^2
=(root 3 ^2-root 7^2)
=3-7
=-4
hope it is helpful.
Answered by
1
hope it helps
please mark it
Attachments:
![](https://hi-static.z-dn.net/files/d8f/ae08612e487bff0408cb10f83710051e.jpg)
Similar questions
English,
6 months ago
Math,
6 months ago
Economy,
6 months ago
Chemistry,
1 year ago
CBSE BOARD XII,
1 year ago
Biology,
1 year ago
Business Studies,
1 year ago
Physics,
1 year ago